FRI0467 Predictors of Early Minimal Disease Activity in PSA Patients Treated with Anti-TNF in A Real-World Registry. (15th July 2016) - Zummer, M.; Rahman, P.; Starr, M.; Kelsall, J.T.; Avina-Zubieta, A.; Baer, P.; Sholter, D.; Teo, M.; Rampakakis, E.; Psaradellis, E.; Osborne, B.; Maslova, K.; et al.
Abstract : Background: Early achievement of minimal disease activity (MDA) is recommended as a valid treat-to-target approach in psoriatic arthritis (PsA). Objectives: The purpose of the current analysis was to evaluate predictors of MDA achievement in PsA patients treated with anti-TNF agents in Canadian routine clinical care. Methods: BioTRAC is an ongoing, prospective registry of patients initiating treatment for rheumatoid arthritis, ankylosing spondylitis, or PsA with Infliximab (IFX) or Golimumab (GLM). Eligible people for this analysis included PsA patients treated with IFX who were enrolled since 2005 or with GLM enrolled since 2010 and with available MDA information at baseline, 6 months, and/or 12 months. MDA was defined as the fulfillment of ≥5 of the following criteria: TJC28≤1, SJC28≤1, PASI≤1, Pain (VAS)≤15mm, PtGA (VAS)≤20mm, HAQ ≤0.5, tender entheseal points ≤1. Independent predictors of MDA achievement were assessed with logistic regression. Results: A total of 196 patients (51.4% male and 87.2% bionaive) were included with a mean (SD) age and disease duration of 49.8 (11.1) and 5.4 (6.3) years, respectively. The proportion of patients with MDA was 11.7% at baseline, 43.5% at 6 months, 44.8% at 12 months, and 49.1% at either 6 or 12 months. Among patients with MDA at 6 months, 75.7% had sustained MDA at 12 months. Patients achieving MDA during follow-up had significantly lower disease activity at baseline; mean (SD) disease parameters were: SJC28: 3.24 (3.58) vs. 5.47 (4.31), P<0.001; TJC28: 3.75 (4.00) vs. 8.66 (6.53), P<0.001; pain: 35.39 (25.11) vs. 55.70 (22.93), P<0.001; PtGA: 38.51 (25.00) vs. 56.15 (25.13), P<0.001; HAQ-DI: 0.71 (0.61) vs. 1.33 (0.57), P<0.001; MDGA: 4.25 (2.38) vs. 5.84 (2.07), P<0.001); enthesitis count: 2.62 (1.60) vs. 4.97 (3.48), P=0.008. Multivariate logistic regression analysis showed that lower baseline HAQ (OR=0.243; P<0.001), lower TJC28 (OR=0.889; P=0.008), and lower enthesitis count (OR=0.817; P=0.817) were significant predictors of MDA achievement over 12 months of treatment. Conclusions: The results of the current analysis have shown that 50% of patients treated with IFX or GLM in routine clinical care achieve MDA within the first year of treatment. Lower baseline HAQ, lower TJC28, and lower enthesitis count were identified as significant predictors of MDA achievement. Disclosure of Interest: M. Zummer: None declared, P. Rahman: None declared, M. Starr: None declared, J. Kelsall: None declared, A. Avina-Zubieta: None declared, P. Baer: None declared, D. Sholter: None declared, M. Teo: None declared, E. Rampakakis Employee of: JSS Medical Research Inc;, E. Psaradellis Employee of: JSS Medical Research Inc;, B. Osborne Employee of: Janssen, K. Maslova Employee of: Janssen, F. Nantel Employee of: Janssen, A. Lehman Employee of: Janssen, C. Tkaczyk Employee of: Janssen